Why Do Not Students Turn On Their Cameras during Online Classes - Fiki Setiawan; Arief Zul Fauzi (Budapest International Research and Critics University, 2022)
Since several higher education institutions do not compel students to turn on their webcams during online sessions, professors assert that they have adopted this practice in response to the COVID-19 pandemic-related shift in instructional activities. They were considering the current research intended to determine the reasons behind students' decision to conceal their identities during online classes and provide potential solutions for enhancing the educational process's sustainability. We specified that the usage of video cameras in class was optional but encouraged out of consideration for the pupils. However, several of our instructors and students remarked that they did not utilize their cameras as often as they would have liked by the end of the semester, decreasing the educational experience. We surveyed students to ascertain why they chose not to activate their cameras. Students do not switch on their webcams during online lectures to engage in other things concurrently. Numerous hypothesized explanations, including the most frequently mentioned concern about personal appearance, were confirmed. Additionally, being concerned about other people and the physical location visible in the background and having a sluggish internet connection were issues. Turning on the camera throughout the educational process offers several benefits, including assessing students' level of knowledge and directing their attention to the lesson, fostering communication and emotional development, and preventing outdoor activities during the learning process.